Comparison and Hydrochemical Characterization of Groundwater Resources in the Arabian Peninsula: A Case Study of Al-Baha and Al-Qassim in Saudi Arabia - Fahad N. Al-Barakah; Aly, Anwar A.; Abaakhel, Emad H. S.; Al-Rizkid, Abdulwahid M.; Alghamdi, Abdulaziz G.; Al-Sewailem, Mohammad S. (Water resources, 2020)
The objective of this study was to compare and assess the quality and study the hydrochemistry of groundwater in the Al-Baha and Al-Qassim areas, representing the Arabian Shield and Arabian Shelf, respectively, of the Arabian Peninsula. The chemical and microbiological constituents of the groundwaters of the two sites were acquired and compared. The Al-Baha analyses indicated that the underground water near urban area is subject to contamination by E. coli and nitrate. However, the dissolved salts and soluble ions were at an acceptable level according to WHO standards. In Al-Qassim, 77% of the studied groundwater samples were inappropriate for drinking because of high salinity; however, 60% had slight to moderate salinity hazard for use in irrigation. At both regions, trace elements were found to be within acceptable limits for irrigation and drinking. Piper, Schoeller, and Durov diagrams showed that the majority of the investigated groundwaters in Al-Baha were calcium–magnesium, chloride–sulfate water type. However, 51% of the studied waters in Al-Qassim were sodium, chloride, sulfate water type. The geology of Al-Baha is comprised of gypsum, anhydride, and dolomite. The geology of Al-Qassim is dominantly comprised of halite. The saturation index indicated that the Al-Baha groundwaters are undersaturated with respect to halite, gypsum, and anhydrite; however, the groundwaters of Al-Qassim are undersaturated with respect to halite. The approach utilized in this investigation could be useful in similar environments worldwide.